The Call of Metaphor: Richard Rorty’s Politics of Language - Arribas, Sonia (Logos. Anales del Seminario de Metafísica, 2007)
This article deals with Donald Davidson’s concept of metaphor and Richard Rorty’s use of it for his version of political liberalism. Rorty assumes that metaphor is a linguistic element that is impossible to understand. Metaphor is an unintelligible “call” that, from within the private sphere, provokes in individuals the desire to create alternative forms of life. Once metaphor has become literal, it –and the new form of life that it entails– can form part of public life. Metaphor is the guarantee of the constant renewal of political liberalism. As against Rorty, yet also relying on Davidson, I argue that both metaphor and literal meaning are comprehensible, and must therefore be said to exist in a relationship of mutuality. This allows me to subject to a thorough re-elaboration Rorty’s strict internal division of the political along the lines of the public and the private.